Structures for surface-enhanced nonplasmonic or hybrid spectroscopy - Mayerhöfer Thomas G.; Pahlow Susanne; Popp Jürgen (Nanophotonics, 2020)
Absorption, scattering, and fluorescence are processes that increase with electric field intensity. The most prominent way to enhance electric field intensity is to use localized or propagating surface plasmon polaritons (SPPs) based on metallic particles and nanostructures. In addition, several other, much less well-known, photonic structures that increase electric field intensity exist. Interference enhancement provided by thin dielectric coatings on reflective substrates is able to provide electric field intensity enhancement over the whole substrate and not only at certain hotspots, thereby being in particular suitable for the spectroscopy of thin surface layers. The same coatings on high refractive index substrates may be used for interference-enhanced total internal reflection-based spectroscopy in much the same way as Kretschmann or Otto configuration for exciting propagating SPPs. The latter configurations can also be used to launch Bloch surface waves on 1D photonic crystal structures for the enhancement of electric field intensity and thereby absorption, scattering, and fluorescence-based spectroscopies. High refractive index substrates alone can also, when nanostructured, enhance infrared absorption or Raman scattering via Mie-type resonances. As a further method, this review will cover recent developments to employ phonon polaritons in the reststrahlen region.